Foraminifera in Late Elsterian-Holsteinian deposits of the Tornskov area in South Jutland, Denmark - Knudsen, Karen Luise (Danmarks Geologiske Undersøgelse Serie B, 1987)
Foraminiferal faunas from marine Late Elsterian and Holsteinian deposits in the Tornskov borehole have been investigated. The faunal succession is correlated with the pollen zones of the same boring, and the assemblages are compared with Late Elsterian and Holsteinian faunas described from adjacent areas. Arctic foraminiferal faunas at the base of the marine sequence at Tornskov indicate that a marine transgression occurred prior to the establishment of full interglacial conditions, i.e. in the Late Elsterian. Marine sedimentation continued during much of the Holsteinian Interglacial. The assemblages here indicate boreal, mainly sublittoral conditions and relatively open access to the North Sea. Evidence for withdrawal of the Holsteinian sea from the area is not recorded in the faunas at Tornskov, the uppermost part of the marine sequence having probably been removed by subsequent glacial erosion. The general trend for corresponding deposits over the whole area of SW Denmark and N. Germany is that the regression took place before any indication of climatic deterioration is seen in either the fauna or the flora.